Evaluasi Pengendalian Internal Sistem Informasi Akuntansi Penerimaan Kas Pada PT Bank BRI Cabang Tahuna - Sarapi, Debby E. R.; Manoppo, Wilfried S.; Keles, Dantje (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
Banking has a very important role in the wheel of the Indonesian economy, because it provides services in various business fields. Banking as it is known is not an ordinary business entity as a company engaged in trade and industry, but a business entity engaged in financial services. Internal control within the company is maintaining and ensuring that every activity in the company is in accordance with and in line with the company's goals. With strict internal control, it is expected that all company operations can run smoothly. not only in the case of operations that will run in an orderly and good manner according to the procedure, but from the company's financial perspective it can also be monitored better so that there are no mistakes and acts of fraud. The purpose of this study is to evaluate the internal control and cash receipt accounting systems available at BRI Tahuna Branch. This type of research is qualitative. Methods of data collection in the form, is conducting interviews, observation and documentation. The results of this study are the Implementation of the Internal Control System at Cash Receipts at PT. Bank Rakyat Indonesia (Persero) Tbk Tahuna Branch has fulfilled the elements of the Cash Receipt Internal Control System and is running well. This is indicated by the clear separation of duties, responsibilities, and authority limits in each work unit in the company.